An investigation into interest and its elicitation in Middle School Science lessons - Newton-John, Osmar Jeremy (Curtin University, 2015)
I surveyed 193 Year 8 students in 50 high schools about their interest in science. Prior interest in science predicted general academic aptitude and lesson interest was inversely proportional to class size. Students with low prior interest in science responded differently from their peers. Novelty of visual teaching materials was the most influential factor in lesson interest. The study reinforced the significance of interest in education.